Harga Pokok Produksi Padi Sawah Lebak dan Faktor yang Mempengaruhinya di Kecamatan Sirah Pulau Padang Kabupaten Ogan Komering Ilir - Dian Retnowati; Diah Utami Damayanti; Etika Fuji Lestari; Maria Elsa Alfitri; Dessy Adriani; Elisa Wildayana; Imron Zahri (Seminar Nasional Lahan Suboptimal, 2018)
Retnowati et al, 2019. The Production Cost of Lebak Rice Fields and its Affecting Factors in the Sirah Pulau Padang District Ogan Komering Ilir Regency. pp. 298-305.This study aims to analyze the cost of production of lebak rice and the factors that affect its cost. This research was carried out in the Sirah Pulau Padang Sub district, Ogan Komering Ilir District, 2017/2018.  The research method used in this study is a survey method with a disproportionate stratified random sampling method. The total population of 1357 families was grouped into farmers with(1) members and (2) non members of farmer groups. The results of the study obtained the cost of production of lebak rice for the farmers belonging to the farmer group on average Rp 1.303 per kg, and not a member of the farmer group on the average of Rp 1.402.  There were only two variables that had the most influence, namely the land area and outside family workforce. The land area has a negative affect on the cost of production, meaning that the more land area, the lower the cost of production. Whereas the workforce outside the family has a positive effect on the cost of production, meaning that the more workers outside the family are used, the more the cost of production will increase.